Risk factors of treatment failure in community acquired pneumonia: implications for disease outcome. Issue 11 (29th October 2004) - Menéndez, R; Torres, A; Zalacaín, R; Aspa, J; Martín Villasclaras, J J; Borderías, L; Benítez Moya, J M; Ruiz-Manzano, J; Rodríguez de Castro, F; Blanquer, J; Pérez, D; Puzo, C; et al.
Abstract : Background: An inadequate response to initial empirical treatment of community acquired pneumonia (CAP) represents a challenge for clinicians and requires early identification and intervention. A study was undertaken to quantify the incidence of failure of empirical treatment in CAP, to identify risk factors for treatment failure, and to determine the implications of treatment failure on the outcome. Methods: A prospective multicentre cohort study was performed in 1424 hospitalised patients from 15 hospitals. Early treatment failure (<72 hours), late treatment failure, and in-hospital mortality were recorded. Results: Treatment failure occurred in 215 patients (15.1%): 134 early failure (62.3%) and 81 late failure (37.7%). The causes were infectious in 86 patients (40%), non-infectious in 34 (15.8%), and undetermined in 95. The independent risk factors associated with treatment failure in a stepwise logistic regression analysis were liver disease, pneumonia risk class, leucopenia, multilobar CAP, pleural effusion, and radiological signs of cavitation. Independent factors associated with a lower risk of treatment failure were influenza vaccination, initial treatment with fluoroquinolones, and chronic obstructive pulmonary disease (COPD). Mortality was significantly higher in patients with treatment failure (25% v 2%). Failure of empirical treatment increased the mortality of CAP 11-fold after adjustment for risk class. Conclusions: Although these findings need to be confirmed by randomised studies, they suggest possible interventions to decrease mortality due to CAP.